P199 Hidradenitis suppurativa associated with Crohn's disease: An increased risk of permanent stoma. (16th January 2018) - Dumont, L -M; Guegan-Bart, S; Landman, C; Nion-Larmurier, I; Bourrier, A; Sokol, H; Marteau, P; Beaugerie, L; Cosnes, J; Seksik, P
Abstract: Background: Hidradenitis Suppurativa (HS) is a chronic cutaneous, inflammatory disease with strong impact on quality of life. Perineal lesions in Crohn's disease (CD) are frequently observed and may resemble to perineal HS. CD and HS both share an inadequate immune response, to commensal bacteria, in genetically predisposed subjects. The association between these two diseases is more and more described and it appears that HS could negatively influence the prognosis of CD. The aim of our study was to evaluate the impact of HS on CD outcomes. Methods: We performed a case–control with 1 on 4 ratio from a mono-centric tertiary centre where 4645 CD were seen between 2003 and 2016. Patients with both CD and HS were matched to CD patients without HS on sex, date of birth ( ± 2.5 years), date of CD diagnosis ( ± 2.5 years), presence of perineal lesion at the time of diagnosis and follow-up quality. HS cases were confirmed after reviewing the medical charts and by a dedicated clinical examination. Each case of HS was characterised by its location and Hurley's classification. Results: The prevalence of HS was 0.95% through 44 cases identified from the 4645 CD. Of these, 64% had active smoking habits. HS was severe with 80% of patients with Hurley II and III, and was mainly localised in axillary (72%) and perineal (50%) areas. HS was diagnosed after CD in 70% of cases, with a 9 years median between the two diagnosis (IQR 5.25–12.75). In the case–control comparison, HS-associated CD was more active (56% vs. 40% years with active disease, p <0.001) and required more TNF antagonists (39% vs. 23% years spent under anti-TNF, p <0.001) than CD alone. HS-associated CD was also associated with a higher risk of permanent stoma, 16.8% (IQR 7.5–33.3) vs. 2.5% (IQR 0.8–7.4) in the control group ( p = 0.002). The univariate and multivariate analysis confirmed HS as an independent risk factor for permanent stoma with a Hazard Ratio of 6.29 [95% CI (2.30–38.33) p <0.001]. Conclusions: Our study shows that HS has a negative effect on CD outcomes with a more active disease and an increased risk of permanent stoma, despite a higher use of anti-TNF antagonists.